Cost-effectiveness of sex-neutral HPV-vaccination in Sweden, accounting for herd-immunity and sexual behaviour. Issue 34 (16th August 2018) - Wolff, Ellen; Elfström, K. Miriam; Haugen Cange, Hedda; Larsson, Sofie; Englund, Helene; Sparén, Pär; Roth, Adam
Highlights: Cost-effectiveness of sex-neutral HPV-vaccination in a high-coverage setting. Dynamic model accounting for sexual behaviour, including age preferences and MSM. Sex-neutral vaccination would reduce HPV-related disease. Sex-neutral HPV-vaccination would be good value for money in Sweden. Also HPV-vaccinating boys would be cost-effective despite 80% coverage among girls. Abstract: Introduction: The aim was to assess cost-effectiveness of expanding the Swedish HPV-vaccination program to include preadolescent boys, by comparing health-effects and costs of HPV-related disease, with a sex-neutral vaccination program versus only vaccinating girls. Methods: We used a dynamic compartmental model to simulate the burden of HPV16/18-related disease in Sweden, accounting for indirect effects of vaccination through herd-immunity. The model accounted for sexual behaviour, such as age preferences and men who have sex with men. The main outcome was number of individuals with HPV-related cancers (cervical, genital, anal and oropharyngeal cancer) and cervical intraepithelial neoplasia (CIN). Costs included in the analysis were those incurred when treating HPV-related cancer and CIN, production losses during sick-leave, and acquisition and administration of vaccine. Health effects were measured as quality-adjusted life years (QALY). The time horizon was set to 100 years, and both effects and costs were discounted by 3% annually. Health effects and costs were accumulated over the time horizon and used to create an incremental cost-effectiveness ratio. Results: A sex-neutral vaccination program would reduce HPV-related cancer and CIN, both due to direct effects among vaccinated as well as through herd-immunity, further decreasing HPV-related cancer burden annually by around 60 cases among men and women respectively in steady-state. The cost per gained QALY was estimated to 40, 000 euro. Applying the procurement price of 2017, sex-neutral vaccination was dominant. Conclusion: Introducing a sex-neutral HPV-vaccination program would be good value for money also in Sweden where there this 80% coverage in the current HPV-vaccination program for preadolescent girls. The cost-effectiveness of a sex-neutral program is highly dependent on the price of the vaccine, the lower the price the more favourable it is to also vaccinate boys.